WORK PERFORMANCE: EXPLORING THE INFLUENCE OF SERVANT LEADERSHIP IN CHRISTIAN HIGHER EDUCATION INSTITUTIONS - Kailola, Lisa Gracia; Sitohang, Mawar; Yang, John J.; Samaloisa, Benhur (Jurnal Manajemen Pendidikan, 2025)
In Christian higher education, servant leadership strengthens a sense of calling and spiritual motivation among employees. Faculty and staff who perceive their work as part of God’s mission often demonstrate higher dedication, teamwork, and ethical responsibility. Servant leadership emphasizes humility, empathy, and a commitment to serving others before oneself. Within Christian higher education, this leadership model resonates deeply with biblical values and institutional missions centred on spiritual formation and academic excellence. This article aims to explore how servant leadership influences employee work performance, particularly within Christian universities. Using a literature review method, this study synthesizes findings from various academic sources to identify how servant leadership principles affect employee motivation, engagement, and productivity. Additionally, it discusses challenges faced by Christian higher education institutions in implementing servant leadership, especially amid the disruption era and the growing integration of Artificial Intelligence (AI) in education.